Non-Coding RNA in Microglia Activation and Neuroinflammation in Alzheimer’s Disease - He C; Li Z; Yang M; Yu W; Luo R; Zhou J; He J; Chen Q; Song Z; Cheng S (Dove Medical Press, 2023)
Chunxiang He,1,2 Ze Li,1,2 Miao Yang,1,2 Wenjing Yu,1,2 Rongsiqing Luo,1,2 Jinyong Zhou,1,2 Jiawei He,1,2 Qi Chen,1,2 Zhenyan Song,1,2 Shaowu Cheng1,2 1School of Integrated Chinese and Western Medicine, Hunan University of Chinese Medicine, Changsha, Hunan, People's Republic of China; 2Key Laboratory of Hunan Province for Integrated Traditional Chinese and Western Medicine on Prevention and Treatment of Cardio-Cerebral Diseases, College of Integrated Traditional Chinese and Western Medicine, Hunan University of Chinese Medicine, Changsha, Hunan, People's Republic of ChinaCorrespondence: Zhenyan Song; Shaowu Cheng, Tel +86 073188458257, Email songzhenyan2013@hnucm.edu.cn; scheng@hnucm.edu.cnAbstract: Alzheimer's disease (AD) is a neurodegenerative disorder characterized by complex pathophysiological features. Amyloid plaques resulting from extracellular amyloid deposition and neurofibrillary tangles formed by intracellular hyperphosphorylated tau accumulation serve as primary neuropathological criteria for AD diagnosis. The activation of microglia has been closely associated with these pathological manifestations. Non-coding RNA (ncRNA), a versatile molecule involved in various cellular functions such as genetic information storage and transport, as well as catalysis of biochemical reactions, plays a crucial role in microglial activation. This review aims to investigate the regulatory role of ncRNAs in protein expression by directly targeting genes, proteins, and interactions. Furthermore, it explores the ability of ncRNAs to modulate inflammatory pathways, influence the expression of inflammatory factors, and regulate microglia activation, all of which contribute to neuroinflammation and AD. However, there are still significant controversies surrounding microglial activation and polarization. The categorization into M1 and M2 phenotypes may oversimplify the intricate and multifaceted regulatory processes in microglial response to neuroinflammation. Limited research has been conducted on the role of ncRNAs in regulating microglial activation and inducing distinct polarization states in the context of neuroinflammation. Moreover, the regulatory mechanisms through which ncRNAs govern microglial function continue to be refined. The current understanding of ncRNA regulatory pathways involved in microglial activation remains incomplete and may be influenced by spatial, temporal, and tissue-specific factors. Therefore, further in-depth investigations are warranted. In conclusion, there are ongoing debates and uncertainties regarding the activation and polarization of microglial cells, particularly concerning the categorization into M1 and M2 phenotypes. The study of ncRNA regulation in microglial activation and polarization, as well as its mechanisms, is still in its early stages and requires further investigation. However, this review offers new insights and opportunities for therapeutic approaches in AD. The development of ncRNA-based drugs may hold promise as a new direction in AD treatment.Keywords: Alzheimer's disease, non-coding RNA, neuroinflammation, microglia activation, miRNA, circRNA, lncRNA